计算5ab^3*(-3/4a^3b^2)*(-2/3ab^4c)^3 x(x-1)(x+3)-x^2(x+1)+3x-1

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 10:38:35
计算5ab^3*(-3/4a^3b^2)*(-2/3ab^4c)^3x(x-1)(x+3)-x^2(x+1)+3x-1计算5ab^3*(-3/4a^3b^2)*(-2/3ab^4c)^3x(x-1)(

计算5ab^3*(-3/4a^3b^2)*(-2/3ab^4c)^3 x(x-1)(x+3)-x^2(x+1)+3x-1
计算5ab^3*(-3/4a^3b^2)*(-2/3ab^4c)^3 x(x-1)(x+3)-x^2(x+1)+3x-1

计算5ab^3*(-3/4a^3b^2)*(-2/3ab^4c)^3 x(x-1)(x+3)-x^2(x+1)+3x-1
5ab^3*(-3/4a^3b^2)*(-2/3ab^4c)^3
=5ab³×(-3/4a³b²)×(-8/27a³b^12c^3)
=10/9a^7b^17c³
x(x-1)(x+3)-x^2(x+1)+3x-1
=x(x²+2x-3)-x²(x+1)+3x-1
=x³+2x²-3x-x³-x²+3x-1
=x²-1